Communicating the springs and forest preservation in the Arjuna mount area, Indonesia - Hermanto, Yustinus Budi; Nugroho, Matheus (Jurnal Studi Komunikasi, 2021)
The study's goals were to determine the impact of community empowerment for the springs and forest preservation in the Arjuna mount area from the environmental communication perspective. The quantitative descriptive research method was used, with the study population covered communities around the forest and springs that were domiciled in three villages, namely Leduk, Jatiarjo, Dayurejo Villages, Pasuruan-East Java, Indonesia. Data was gathered from respondents with a questionnaire and analysed using SEM (structural equation modelling) to find an overview of respondents' responses about community participation in preserving the Arjuna mount forest. Human resources around the forest, namely the level of education and employment, contribute to the success of revegetation of forests; family economic conditions such as personal and family income, ownership of fields and rice fields for business, and livestock and fisheries businesses assist successful forest revegetation; social characteristics of the community around the forest such as cooperation and kinship between community members contribute to forest revegetation; community institutions, namely forest village community institutions, are a vehicle for the community to revegetate forests successfully; the availability of village community facilities and infrastructures such as paved road access, transportation and communication networks, education and health facilities contribute to the successful revegetation of Arjuna mount forest.